Survey on mortality rate of young stock on dairy farms of the Province of Padova - Lora, Isabella; Paparella, Paolo; Brscic, Marta; Gottardo, Flaviana (Acta Agraria Kaposváriensis, 2014)
The present study aimed at investigating preliminarily the mortality rate in 2012 of replacement calves and heifers in 95 dairy farms in the Province of Padova. Data regarding total number of cows and replacement stock reared were gathered from the APA Breeders’ Association records while data on number of dead replacement animals were collected from insurance records. Results showed that the median value of the overall mortality rate of replacement cattle <24 months was 3.3% (0âˆ’6.7%, first - third quartile) with a maximum of 28.6%. Considering the age categories, mortality of 0âˆ’12 months old replacement cattle was higher than that of 13 - 24 months old. The median of mortality for cattle <12 months was 4.9% (0âˆ’11.8%, first - third quartile), with a maximum of 72.1% in one farm. The median value of mortality for the older age category (13âˆ’24 months) was of 0% (0âˆ’1.6%, first - third quartile) with a maximum value of 25%. This seems a positive outcome, however, the high variability arisen from this survey points out serious problems in some farms. Moreover, despite results pointed out a higher risk of mortality at the early stage of cattle life, a considerable number of farms showed mortality rates exceeding 10% for the heifers between 13 and 24 months of age. Mortality rates at a late stage indicate a serious situation in these farms which leads also to relevant economic losses. In conclusion, it is suggested to investigate on predisposing risk factors at different ages in order to develop and apply specific actions to overcome such problems.